Disease Profile of Skin Infection due to Virus toward Children - Abdi, Dian Amelia; Muhtar, Muftiar; Anastasia, Rizka; Yuniati, Lisa; Maulani, Destya (Poltekkes Kemenkes Palu, 2024)
Skin is a special organ in humans. The skin functions as a defense that is continuously affected by the external environment and always adapts to environmental changes. Infectious skin diseases can be caused by viruses. This study aims to determine the profile of viral skin diseases in children at the Ibnu Sina Teaching Hospital (RSP) Makassar and its network. Descriptive retrospective study using medical records of patients at RSP Ibnu Sina Makassar and its network, namely RSUD Makassar City, RSUD Haji South Sulawesi Province for the period January 2017–December 2022. The reseach results show that there were 113 cases of skin disease caused by viral infections in children who received treatment at RSP Ibnu Sina Makassar and its network with the number of cases being morbilli disease (33.6%), followed by varicella (27.4%), verruca vulgaris (21.2%), HZ (7.1%), HFMD (7.1%), and molluscum kotagiosum (3.5%). Most ages were 12–18 years (35.4%), 6–11 years (32.7%), 2–5 years (14.2%), 13 months–2 years (10.6%), 28 days–12 months (7.1%), and 0–27 days not found. Gender is male (47.8%) and female (52.2%). The length of stay for morbilli is 1-6 days, varicella 3-7 days, HFMD 3 days, molluscum contagiosum 3 days, HZ and verruca vulgaris each not hospitalized. Antiviral therapy was given as much as (38.9%) and antiviral therapy was not given (61.1%). The conclusion is viral skin infections were the most prevalent in children in 2017, dominant in early adolescence and female. The most Morbili were found, with female gender and middle childhood age. Varicella with a maximum length of stay of 7 days. Most were not given antiviral therapy.